2020
DOI: 10.2139/ssrn.3659874
|View full text |Cite
|
Sign up to set email alerts
|

Economic Consequences of High Public Debt: Evidence from Three Large Scale DSGE Models

Abstract: and the members of the ESCB Working Group on Public Finance for their useful comments and suggestions. We are also grateful to an anonymous referee for very useful comments and suggestions on the ECB working paper. Any remaining errors are ours. The views expressed in this paper are those of the authors and do not necessarily reflect those of the European Central Bank or the ESCB Working Group on Public Finance and its members. This paper has also been published as an ECB Working Paper with number 2450, July 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…High indebtedness can generate a negative effect on economic growth and private investment (Fatás et al, 2020;Yared, 2019), as well as diminish the capacity of governments to respond to adverse shocks such as natural disasters, financial crises, or wars (Obstfeld, 2013;Romer & Romer, 2018). Additionally, countries with higher indebtedness present a greater sensitivity to spillover effects, because their economies are more vulnerable to macroeconomic shocks (Burriel et al, 2020). Moreover, in default episodes, financial institutions and private companies have less access to financial systems and export markets (Borensztein & Panizza, 2008;Hébert & Schreger, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…High indebtedness can generate a negative effect on economic growth and private investment (Fatás et al, 2020;Yared, 2019), as well as diminish the capacity of governments to respond to adverse shocks such as natural disasters, financial crises, or wars (Obstfeld, 2013;Romer & Romer, 2018). Additionally, countries with higher indebtedness present a greater sensitivity to spillover effects, because their economies are more vulnerable to macroeconomic shocks (Burriel et al, 2020). Moreover, in default episodes, financial institutions and private companies have less access to financial systems and export markets (Borensztein & Panizza, 2008;Hébert & Schreger, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Deleveraging can reduce its negative effects on economic growth. However, some studies have found that a sharp reduction in leverage could reduce economic growth and may even lead to long-term recession [72][73][74][75][76]. Liu Xiaoguang et al [4] believed that the efficiency of leverage is crucial to economic growth and at the core of striking a balance between leverage and economic growth.…”
Section: How To Balance Between Implicit Contingent Liabilities and E...mentioning
confidence: 99%
“…Государственный долг является важнейшим источником ресурсов правительства для финансирования государственных расходов и заполнения пробелов в бюджете, поэтому в отношении к ВВП обычно используется в качестве показателя способности правительства выполнять свои обязательства в будущем. Согласно (Burriel et al 2020), государственный долг представляется неотъемлемой частью функционирования рыночной экономики. В литературе говорится о том, что для любой экономики существуют определенные издержки и выгоды, связанные с долгом.…”
Section: Introductionunclassified